Comparative Eye Effect of Unilateral Intravitreal Bevacizumab, Ranibizumab, and Aflibercept for Diabetic Macular Edema. (March 2019) - Malbin, Brett; Patel, Harshad P.; He, Yuguang; Le, Kim; Lin, Xihui
Purpose: The purpose of this article is to compare the fellow-eye effect of unilateral intravitreal antivascular endothelial growth factor (anti-VEGF) treatment (bevacizumab, ranibizumab, and aflibercept) in patients with bilateral diabetic macular edema (DME). Methods: A retrospective review was conducted of hemoglobin A1c-matched groups receiving unilateral anti-VEGF injections (1.25 mg bevacizumab, 0.5 mg ranibizumab, and 2 mg aflibercept) in which the second eye had subclinical DME. Two main outcome measures evaluated were central subfield thickness (CST) on optical coherence tomography and best-corrected visual acuity (BCVA). Patients were excluded if they had poor BCVA (< 20/100) or had received laser, vitrectomy, filtering surgery, or pharmacologic treatments in the 3 months prior in the noninjected eye. Results: A total of 2073 total intravitreal anti-VEGF injections for DME were reviewed and 94 met the inclusion criteria: 40 bevacizumab, 33 ranibizumab, and 21 aflibercept. At 1 month, the CST of the fellow eye in the bevacizumab group had a statistically significant decrease (296.82 µm to 292.46 µm, P = .01) while both the ranibizumab and aflibercept groups trended toward worsening edema. When compared to ranibizumab and aflibercept, the CST in the noninjected eye in the bevacizumab group had improvements of –15.03 µm and –13.47 µm, respectively ( P < .019). When bevacizumab was switched to ranibizumab or aflibercept, the edema in the fellow eye worsened by +49.60 µm and +5.50 µm, respectively. Conclusion: Bevacizumab injection has a statistically significant therapeutic effect in the fellow eye when compared to those treated with ranibizumab and aflibercept. The edema in the fellow eye worsened when injection in the primary eye was switched away from bevacizumab.